Functional anal canal length measurement using high‐resolution anorectal manometry to investigate anal sphincter dysfunction in patients with fecal incontinence or constipation. Issue 3 (13th January 2019) - Vollebregt, Paul F.; Rasijeff, Annika M. P.; Pares, David; Grossi, Ugo; Carrington, Emma V.; Knowles, Charles H.; Scott, S. Mark
Abstract: Background: Using high‐resolution anorectal manometry, we aimed to evaluate the: (a) optimal threshold to measure functional anal canal length (FACL) with intra‐ and inter‐observer variability; (b) relationship between abnormal FACL and other phenotypic findings; and (c) utility of FACL measurement to discriminate between healthy volunteers (HV) and patients with fecal incontinence (FI) or chronic constipation (CC). Methods: Consecutive patients referred for investigation of FI or CC in isolation were included. FACL was calculated at 5, 10, 20, 30, and 50 mm Hg above rectal pressure. 5th‐95th percentile in HV defined limits of normality. Key Results: FACL was analyzed in 192 patients with FI (154 females), 204 patients with CC (175 females), and 134 HV (101 females). The optimal threshold for measurement of FACL was 20 mm Hg. Using this threshold, observer reproducibility was very high (ICC 0.99, P  < 0.0001). FACL was shorter in females with FI and longer in females with CC compared to HV (2.3 vs 2.9 cm; and 3.4 cm vs 2.9 cm; both P  < 0.0001). Twenty percent of females and 13% males with FI had a short FACL, associated with older age, anal hypotonia or hypocontractility, and a atrophic internal anal sphincter. However, abnormal FACL in isolation was only found in 1/190 FI (0.5%) and 2/201 CC (1%) patients; all other patients had other abnormal manometric findings. Conclusions and Inferences: Considering overlap with other routinely evaluated manometric parameters, FACL measurement does not provide additional information in the diagnostic assessment of FI or CC. Abstract : Anorectal manometry is the best established tool for investigation of anal sphincter dysfunction. However, current metrics to discriminate between health and disease are considered suboptimal. Functional anal canal length (FACL) as a marker of disease has never been studied using high‐resolution anorectal manometry. FACL was shorter in females with fecal incontinence compared to healthy volunteers; 20% females and 13% males with fecal incontinence had short FACL. Almost all patients with abnormal FACL had other abnormal manometric findings. Considering the overlap with other anorectal physiological parameters, measurement of FACL does not appear clinically useful.